Pengembangan Aplikasi Pengelolaan Tugas dan Fungsi Balai Monitor (Studi Kasus: Sarana dan Pelayanan) - Yuli Fitrisia (Jurnal Komputer Terapan, 2021)
Facilities and Services at the Balai Monitor Radio Kelas I Pekanbaru is one of the fields of service to the community.Currently, facilities and services have not implemented and utilized the existence of integrated information technology to support daily work activities so that most service operational activities are still carried out manually.Some activities are still carried out manually, automatically making it difficult and slow for officers to serve the community and make reports.The Management System for Duties and Functions of the Facilities and Services Section is expected to help overcome problems in providing services to the community and managing data services. The system was built using the prototyping method 3 times iteration. Testing of this application is done by UAT through questionnaires and Blackbox Testing to test functional suitability. Based on the results of the questionnaire found that the application meets the criteria of UAT where 100% of respondents agreed that the application display design was easy to remember.95% of respondents agree that the application is easy to reach. and 98.3% of respondents agreed to have an efficient function. Based on the results of Blackbox testing,the application can run smoothly according to existing needs